Fundamental Research - Lancereau, Damien (Cranfield University, 2017)
Digital image presented at the 2017 Defence and Security Doctoral Symposium.On this picture: My supervisor (Hugh Goyder) and me, in front of my experimental workbench. This image presents two generations of researchers. It reminds us of the continual evolution of the sciences. Behind, the metal frame isolates the suspended test items from ambient vibration. The two large cast iron beds minimize the transmission of ground vibration (car traffic seismic, steps). A beam is suspended by two almost invisible fishing wires from the frame; it is ready for vibration testing. With this setup, it is possible to do fundamental research on the dynamics of built-up structures. Our goal is to understand what is happening inside a connection between two parts of the beam during vibration.
Keywords: 'Vibration'; 'Dynamic'; 'Joint'; 'DSDS17 digital image'; 'DSDS17'; 'Dynamics; Vibration and Vibration Control'